Consumption pattern: A comparative study with specific reference to the Engel’s law of two different income groups in Bangsar / Leong Yoke Kim - Leong , Yoke Kim (1986)
This academic exercise is an attempt to test the validity of the Enge’s law in the context of consumption pattern. Attention is directed towards two different income groups with the aim of achieving its objectives through comparisions. The study has been arranged into 5 chapters, beginning with Chapter I as introduction which discussess the objective of the study. Other metters discussess in this chapter include the target groups chosen, the area selected and the methodology used for the study and lastly the limitations of survey data. Chapter II outline the various definitions, concepts and theories used in the study. Special attention was directed to the Engel’s law and consumer behavior. Chapter III is a detailed analysis on the life-styles of the high income respondents with specific reference on their monthly income-expenditure relation and monthly consumption pattern. Chapter IV sums up the discussion with an attempt to compare and contrast the consumption pattern of the two different income groups chosen for the study. At the same time, conclusion regarding the validity of the Engel’s law are drwan from the findings.